Industry withdrawal from psychiatric medication development - Donald F. Klein; Ira D. Glick (Brazilian Journal of Psychiatry, 2014)
Between 1950 and 1969, on a serendipitous basis, psychiatric drug development flourished. However, there has been a steep decline in the development of new medication classes. Instead of new molecular entities, slight molecular modifications producing “me-too” drugs attempted to garner market share. With failing profitability, industry is now withdrawing from psychiatric medication development. Managed care drastically shortened contact between patients and clinicians, so the possible observation of unexpected benefits has been nullified. The randomized, parallel-groups design met FDA requirements for specific pharmacological efficacy. However, it does not determine whether a patient who improved while drug-treated required the drug or would have gotten better on his own. Further, pathophysiology benefit remains obscure. The major psychotropic drugs have no benefits for normal subjects. Their remarkable benefits must stem from a necessary interaction with a pathophysiological state. Therefore, understanding therapeutic benefit by treating normal subjects becomes unlikely. The claim that therapeutic knowledge in psychiatry proceeds from bench to bedside has proven vacuous, primarily because of our limited understanding of brain pathophysiology. The utility of the alternative intensive design for understanding diagnosis, therapeutic benefit, and pathophysiology is emphasized.